A Study of the Political System of the Hong Kong Special Administrative Region under the Basic Law - Weiyun, Xiao (Columbia Journal of Asian Law, 1988)
In December of 1987, the Hong Kong Special Administrative Region of the People’s Republic of China Basic Law Drafting Committee (Drafting Committee) held its Sixth Plenary Session and dis- cussed the preliminary provisions drafted by the Special Subcommittee on the Political System. These provisions comprise two chapters in the Basic Law: chapter four on the political system of the Hong Kong Special Administrative Region (SAR), and the chap- ter ten appendix. Chapter four is divided into six sections, dealing in turn with the chief executive, the executive branch, the legislature, the judiciary, the district organizations and the civil service. Chapter ten deals primarily with the creation of the initial Hong Kong SAR government. This article has been written with reference to these preliminary provisions, taking into consideration that the text will undergo many revisions and changes. Therefore, this represents only a preliminary inquiry into the issues concerning the proposed political system of the Hong Kong SAR under the Basic Law.